2008
DOI: 10.1086/526470
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Allelochemicals from Two Invasive Plants on the Performance of a Nonmycorrhizal Plant

Abstract: In addition to resource competition, allelopathy is believed to contribute to the invasiveness and impact of several plant invaders of North America. In this study, we examined whether aqueous leaf extracts of Alliaria petiolata and Lonicera maackii, two invaders of deciduous forests in North America, affected growth and reproduction of a target nonmycorrhizal plant and whether effects varied across a soil fertility gradient. While nutrient addition substantially improved the performance of Arabidopsis thalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…There were strong allelopathic effects of L. maackii leaf extracts on germination, growth, resource allocation pattern, and mycorrhizal inoculation. Other studies have found allelopathic effects of Lonicera maackii on germination (Dorning and Cipollini 2006;Cipollini, Titus, and Wagner 2012;Cipollini and Flint 2013) and growth (Cipollini, Stevenson, and Cipollini 2008). McEwan et al (2010) similarly found stronger allelopathic effects of extracts of L. maackii compared to extracts of native species and also found that the effects varied with target species.…”
Section: Materials and Methods Extract Preparationmentioning
confidence: 89%
“…There were strong allelopathic effects of L. maackii leaf extracts on germination, growth, resource allocation pattern, and mycorrhizal inoculation. Other studies have found allelopathic effects of Lonicera maackii on germination (Dorning and Cipollini 2006;Cipollini, Titus, and Wagner 2012;Cipollini and Flint 2013) and growth (Cipollini, Stevenson, and Cipollini 2008). McEwan et al (2010) similarly found stronger allelopathic effects of extracts of L. maackii compared to extracts of native species and also found that the effects varied with target species.…”
Section: Materials and Methods Extract Preparationmentioning
confidence: 89%
“…Plants in introduced habitats may also profit from "enhanced mutualisms"; beneficial microbial allies or mutualists that they have not encountered in their native regions [13,14]. Plants can also affect the presence of nutrient cycling microbes which in turn can create positive feedback mediated by effects on nutrient cycling [3,[15][16][17][18]. The tendency for plant soil feedbacks to be positive in introduced habitats (versus negative in native habitats) may be partly responsible for nonnative plants becoming invasive in introduced areas [4,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds, as a group, are known to play a role in plant-soil interactions through allelopathic effects on plants and soil microbes, as well as through effects on soil pH and mineral availability [4,18,[21][22][23]. A species in its introduced range may use such biochemical weapons to inhibit neighbors directly or disturb other ecosystem properties giving the invader some advantage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations